Prospects and Challenges of Privatization of Agricultural Extension Service in Bangladesh - Uddin, Md Ektear; Qijie, Gao (Asian Journal of Agriculture and Rural Development, 2013)
Globally there has been a growing interest towards the privatization of agricultural extension services. Privatization of extension service delivery is being considered for Bangladesh with a view to lower the government expenditures, to increase the efficiency of service delivery and to improve the quality of the extension services in changed circumstances on the part of the farmers. Farmers’ willingness to pay for the extension service in Bangladesh is still unknown. The lesson learned from the world review indicates that though some developed countries went for complete privatization of agricultural extension services, the most of the developing countries still remaining in the process of gradual privatization on a partly basis. Therefore, after critical analysis, this paper assumed some challenges of privatization of agricultural extension service delivery in Bangladesh. Despite the challenges, it is hoped that Bangladesh still has some prospects to adopt privatization of agricultural extension service if the recommended policy guidelines out lined in this paper are followed accordingly.